Pola Komunikasi Mahasiswa Etnis Jawa Dalam Interaksi Sosial di Universitas Riau - Sausan, Putri; Firdaus, Muhammad (Telangke:Jurnal Telangke Ilmu Komunikasi, 2023)
The need to improve the quality of life is increasingly diverse and requires sacrifice, one of which is education. Currently, if we want to get the major we want, we need to get out of the city where we live, which is often called wandering. When we go abroad, we need fast and good adaptations so that we can get an education as much as possible, but it cannot be denied that differences in residence create many obstacles in getting an education, one of which is cultural differences that hinder communication. This study uses a qualitative method with a descriptive approach and uses uncertainty reduction theory and uses a purposive sampling technique. Types and sources of data obtained through primary data and secondary data. Data collection is done by interviews, observation and documentation. Data analysis techniques by reducing data, presenting data and drawing conclusions. Furthermore, checking the validity of the data was carried out by extending participation and triangulation. The results showed that the communication patterns of Javanese ethnicity were in the form of communication patterns based on communication facilities and media which were supported by mutual feedback so that messages could be understood properly. While the inhibiting factors are stereotype, ethnocentrism, and alienation while the supporting factors are the use of the same language, namely Indonesian, the same means of communication and the ability to think of the Javanese themselves.